Poland: A Decade of Reforms (2010–2020) - Kwiek, Marek (International Higher Education, 2021)
A decade of reforms has changed almost every aspect of university functioning. Poland has moved from privatization to deprivatization and from deinstitutionalization to reinstitutionalization of the research mission of its universities. The research internationalization agenda has led to introducing quantitative, research-focused indicators and new funding and assessment systems. However, the system of incentives to internationalize Polish research has so far proved to be ineffective. These reforms were pursued in politically turbulent times.